COMMUNITY ARCHITECTURE DAN COMMUNITY BASED DEVELOPMENT DALAM PENGELOLAAN RUANG PUBLIK KAMPUNG KOTA - Widaningsih, Lilis; Busono, Tjahjani; Krisnanto, Erna (TERAS)
This paper based on our research on public space design for suburban area â kampung-kota area, that physically has no adequate space for public purposes. In this shortage of space condition, it is necessary to recover physical and social resources and potencies in the community kampung-kota area by partcicipatory approach in acquisition and designing of public space. We deploy Participatory Action Research (PAR) by developing community architecture paradigm and community based development in design process or development for encouraging community participation.Research found out public space characteristic in kampung-kota area and patterns of public space usage. By these findings we develop empowerment model and desgn framework for acquisition, developing, utilizing and maintaining kampung-kota public space.